A standby-power-free TCAM based on TMR logic - Kimura, K.; Hanyu, T. (2007 50th Midwest Symposium on Circuits and Systems, 2007)
In this paper, a new circuit style, called a TMR logic, is proposed for a low-power ternary CAM (TCAM). Since a TMR device can be regarded as a variable resistor with a non-volatile storage capability, the equality search between external inputs and stored data can be merged into the TMR/MOS transistor network. The combination of dynamic current-mode logic (DyCML) and TMR logic makes it possible to perform a high-speed while eliminating the steady current by using series gating DPCs. As a result, standby-power of the proposed TCAM is reduced to 0.5%, in comparison with that of the corresponding CMOS implementation.